MANUSIA DAN HISTORISITASNYA MENURUT MARTIN HEIDEGGER - Sindung Tjahyadi (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2008)
AbstractHeidegger viewed “freedom” and “transcendence” (retrospective consciousness) as the element that determines “the way of human existence” and also the human understanding of “history” radically. Philosophy of history is the main point ofHeidegger’s philosophy. It is showed by his most fundamentalconcept of “temporality”. Heidegger so far developed the basiccharacteristic of relationship of “Being” (reality) and “time”(horizon) as a dialectical relationship. Because of his “poetic”nuance, Heidegger often makes someone confused for his called for “Being” as a “person”, e.g., it as “the giver of blessing”. Heidegger brings to the “true” understanding that all philosophical inquiries start and end in the understanding of human being.Keywords: the way of being, being, history, human being